2014
DOI: 10.1021/jp506563j
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Based Study of the Electron Transfer Reaction at the Lithium Metal Anode in a Lithium–Air Battery with Ionic Liquid Electrolytes

Abstract: Room temperature ionic liquids, which have unique properties such as a relatively wide electrochemical stability window and negligible vapor pressure, are promising candidates as electrolytes for developing lithium–air batteries with enhanced performance. The local current density, a crucial parameter in determining the performance of lithium–air batteries, is directly proportional to the rate constant of the electron transfer reaction at the surface of the anode that involves the oxidation of pure lithium met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Based on first-principles computations, Laino et al [79] studied the reactivity of Li 2 O 2 versus propylene carbonate (PC) and reported that Li 2 O 2 can irreversibly decompose the carbonate solvent, then leading to alky carbonates. Khetan et al [80] proposed that the highest occupied molecular orbital (HOMO) level of the aprotic solvents in LiÀO 2 batteries can be used as a descriptor to evaluate the solvent stability as shown in Figure 6. The solvents with lower HOMO level exhibit better performance in terms of electrons generated in OER.…”
Section: Solvent Stabilitymentioning
confidence: 99%
“…Based on first-principles computations, Laino et al [79] studied the reactivity of Li 2 O 2 versus propylene carbonate (PC) and reported that Li 2 O 2 can irreversibly decompose the carbonate solvent, then leading to alky carbonates. Khetan et al [80] proposed that the highest occupied molecular orbital (HOMO) level of the aprotic solvents in LiÀO 2 batteries can be used as a descriptor to evaluate the solvent stability as shown in Figure 6. The solvents with lower HOMO level exhibit better performance in terms of electrons generated in OER.…”
Section: Solvent Stabilitymentioning
confidence: 99%
“…The electron transfer reactions at the anode-electrolyte interface as well as cathode-electrolyte interface determine the transfer current densities [39,44]. A Recent study by Kazemiabnavi et al investigated the rate of electron transfer at these interfaces as a function of the dielectric properties of the electrolyte [80][81][82]. The DFT based calculations were performed on a simple defect-free crystalline Li surface that is in contact with imidazolium-based solvents.…”
Section: Identifying Suitable Cathode Structure and Catalystsmentioning
confidence: 99%
“…The TFSI anion's structure is also provided. Reprinted with copyright permission from Kazemiabnavi et al[80]. Copyright© 2014, American Chemical Society.…”
mentioning
confidence: 99%
“…Although there are computational efforts trying to investigate oxidation and reduction effects at the electrolyte-electrode interfaces 1113 , progress is slow due to the computational complexity of such simulations. A practical approach is to investigate the intrinsic stability of the bulk liquid electrolyte, which can be used as a first filter when screening improved materials by providing an upper bound to the voltage stability of the entire system 1416 .…”
Section: Introductionmentioning
confidence: 99%